Use of biochar-compost to improve properties and productivity of the degraded coastal soil in the Yellow River Delta, China - Luo, Xianxiang; Liu, Guocheng; Xia, Yang; Chen, Lei; Jiang, Zhixiang; Zheng, Hao; Wang, Zhenyu (Journal of soils and sediments, 2017)
Purpose Nutrient deficiency and salt stress (sodium, Na + ) strongly limited the productivity of the degraded coastal soils in the Yellow River Delta. Biochar-based functional materials have been considered as a promising amendment to solving the problem of global soil security (e.g., erosion, fertility loss, acidification, and salinization). Therefore, this study aimed to explore the potential of using a biochar-compost amendment (BCA) to improve the coastal soil properties and productivity. Materials and methods The BCA was produced from composting of biochar and additives including seafood shell powder, peanut shell, commercial humate, and inorganic nutrients. Two halophytes, sesbania ( Sesbania canabina (Retz.) Pers ) and seashore mallow ( Kosteletzkya virginica ), were chosen as the tested plants in a 52-day pot experiment. BCA was added as the rates of 0, 1.5, 5, and 10 % ( w / w ). At the end of the incubation, the shoot height, biomass, and root morphological parameters including length, tips, and surface area were measured, as well as the properties (e.g., soil organic matter (SOM) content and cation exchange capacity (CEC)) of the rhizosphere and non-rhizosphere soils. Results and discussion The BCA application at 1.5 % enhanced the growth of sesbania and seashore mallow and increased their total biomass by 309 and 70.8 %, respectively, while significantly inhibited both the halophyte growths at 10 %. Similarly, both the halophyte root morphologies (e.g., length and tips) significantly increased by BCA addition at 1.5 %. The promoting growth of the both halophytes could be resulted from the improvement of soil properties such as the increased SOM and CEC, the decreased amount of the exchangeable sodium (Ex-Na) and exchangeable sodium percentage (ESP), and the rhizosphere effect (e.g., decreased soil pH). The higher rate of BCA addition (e.g., 10 %) sharply increased soil salinity, responsible for the inhibition of both the halophyte growths. Although BCA addition may directly supply much nitrogen (N) for the soils, N bioavailability for both halophytes was not largely improved. Conclusions The short-term laboratory pot experiments revealed that producing the biochar-compost with desired properties (e.g., BCA) could be a feasible alternative to remediate the degraded coastal soil in the Yellow River Delta. Moreover, the addition of BCA should be kept at an optimal level, which may produce expected positive results. Our results will be helpful for supporting the strategy of designing right biochar-compost for the right soil.